Immunomodulatory mechanisms of the gut microbiota and metabolites on regulatory T cells in rheumatoid arthritis - Xu, Xuan; Zhou, Jingying; Xie, Haihua; Zhang, Ruhan; Gu, Bowen; Liu, Li; Liu, Mi; Chang, Xiaorong (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) is an autoimmune disease, in which the abnormal activation and proliferation of effector T cells play a pivotal role in its pathogenesis. Regulatory T cells (Tregs) are a unique subset of immune cells with immunosuppressive functions, which help to inhibit the differentiation and proliferation of effector T cells in RA and maintain immune tolerance. The interaction between gut microbiota and immune cells has long been a research hotspot in autoimmune diseases. Although gut microbiota metabolites are considered to regulate the host’s immune system as a bridge of the gut-joint axis, how gut microbiota acts on immunosuppressive Tregs remains unclear. This review summarizes that how the gut microbiota directly or indirectly (via metabolites) enhances the immunosuppressive capacity of Tregs. This enhancement is primarily achieved through pathways such as promoting the induction of Tregs, upregulating the expression of characteristic transcription factors of Tregs, and facilitating their secretion of anti-inflammatory cytokines, thereby ameliorating the inflammatory microenvironment and subsequently improving autoimmune conditions in RA.